2022
DOI: 10.1007/s00432-022-04223-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of surgery to the primary tumor in metastatic anaplastic thyroid carcinoma: pooled analysis and SEER-based study

Abstract: Purpose Anaplastic thyroid carcinoma (ATC) is an orphan disease with a fatal outcome. Surgery to the primary tumor in metastatic ATC is controversial. Determination of specific surgical techniques may help facilitate local control and, hence, beneficial overall and disease-specific survival. Methods Using individualized patient data derived from our systematic review of literature and our single center study (n = 123), conducting a Surveillance, Epidemiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…As local radiotherapy in ATC is regularly administered at the time of diagnosis, using lenvatinib and pembrolizumab as systemic first-line therapy might potentially come with a higher risk to develop a fistula than using it later. Still, in a large retrospective analysis EBRT has recently been associated with improved disease-specific survival in ATC [ 27 ]. In ATC, local tumor aggressiveness drives complications and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…As local radiotherapy in ATC is regularly administered at the time of diagnosis, using lenvatinib and pembrolizumab as systemic first-line therapy might potentially come with a higher risk to develop a fistula than using it later. Still, in a large retrospective analysis EBRT has recently been associated with improved disease-specific survival in ATC [ 27 ]. In ATC, local tumor aggressiveness drives complications and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery constitutes the cornerstone of treatment despite the existing debate. It may range from palliative debulking intervention to more radical resections, including total or near total thyroidectomy and extended lymphadenectomy, including the central and lateral lymph node level either unilaterally or bilaterally[ 6 , 8 , 36 , 53 , 61 ]. The above curative surgery may be performed in some patients with earlier disease and may provide, accompanied by adjuvant chemotherapy, occasional long survival over 5 years[ 18 , 19 ].…”
Section: Managementmentioning
confidence: 99%
“…The above curative surgery may be performed in some patients with earlier disease and may provide, accompanied by adjuvant chemotherapy, occasional long survival over 5 years[ 18 , 19 ]. By multivariate analysis in a systematic review and meta-analysis, surgery and radiotherapy were found to be independent factors predicting increased overall survival[ 36 ]. Complete surgical excision followed by adjuvant therapy is the optimal opportunity for cure[ 4 , 47 ].…”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations